The association of variables of fibular reconstructed mandible and bite force in oral cancer patients with dental implant rehabilitation. Issue 11 (November 2018) - Huang, Yi-Fang; Chang, Chung-Ta; Muo, Chih-Hsin; Hong, Hsiang-Hsi; Shen, Yu-Fu; Lin, Chia-Chang; Liu, Shih-Ping
Abstract: Purpose: The aim of this study was to investigate how the physical variables of fibular reconstructed mandibles with dental implants affects the relative bite force in oral cancer patients. Materials and methods: Over 7 years of follow-up, 13 oral cancer patients were enrolled who included 51 successful implants in the fibular flap. The tactile sensor analyzer evaluated the bite force. The crown-implant ratio, fibular, and rehabilitated dental length were measured using radiographic images. Linear regression was used to analyze the bite force related to the variables of the implants in the fibular reconstructed mandible. Results: Even when the results showed no statistical significance ( P > 0.05), increasing the crown-implant ratio, length of the fibular flap, and implant prosthetic reconstructed dentition had a tendency to decrease the bite force (estimate from −0.08% to −4.27%); there was a positive trend of occlusal force and the length of rehabilitative dentition compared with the dental antagonist (estimate = 6.95). Conclusion: In this study, the crown-implant ratio, implant dentition, and fibular flap length revealed no significant impact on the bite force or implant success in oral cancer patients; however, a trend to weaken the bite force was suggested once the numerical values of these variables increased.